American empire and 'excluded states' : the Millennium Challenge Account and the shift to pre-emptive development - Soederberg, Susanne (2004)
Establishes the underlying power relations and contradictions from which the Millennium Challenge Account (MCA) emerged. Provides a critical elaboration of the MCA by exploring what this agenda sets out to accomplish, how it is to achieve its aims, and which organisations are involved.